Investigation of fouling behaviour of novel centrifugal reverse osmosis (CRO) process - Tan, Rufus Jit Guang (Nanyang Technological University, 2024)
The Centrifugal Reverse Osmosis (CRO) was innovated to be a lower energy-consuming alternative as a Reverse Osmosis technology. Despite earlier conceptualisations of different CRO designs, the concept and design of the CRO in this study was only proven through theoretical model predictions. Hence, this study aimed to investigate the lower energy consumption of the CRO as compared to conventional RO counterparts such as SSRO. This study also aimed to determine the severity of organic fouling of membrane in CRO as compared to SSRO. The theoretical pressure difference calculated from a specific angular rotational rate was compared with the actual pressure difference across the CRO membrane cell in order to provide experimental validations for the CRO. The gross Specific Energy Consumption of the simulated CRO and SSRO were both computed from experimental results, showing that the CRO experienced a reduction in energy consumed from that of the SSRO. The CRO also showed a substantial reduction in organic fouling of the membrane when the simulation of CRO and SSRO were conducted under fouling conditions. The experimental results of the CRO suggest that it has immense potential in becoming a transformative technology that significantly increases savings in costs for desalination to enhance global water security.